Resolving the Relaxation of Volatile Valence Change Memory - Johannes Hellwig; Carsten Funck; Sebastian Siegel; Alexandros Sarantopoulos; Dimitrios Spithouris; Stephan Menzel; Regina Dittmann (Advanced Electronic Materials)
Abstract Memristive devices based on the valence change mechanism are highly interesting candidates for data storage and hardware implementation of synapses in neuromorphic circuits. Although long‐term retention is often required for data storage applications, a slight resistance drift of the low resistive state (LRS) is observed even for stable devices. For other devices, the LRS has been observed to decay rapidly to the high resistive state (HRS). These types of devices are of interest for neuromorphic circuits where short‐term plasticity is required. In this work, the LRS relaxation of volatile, crystalline Pt/SrTiO3/Nb:SrTiO3: devices is investigated in detail, yielding time constants ranging from milliseconds to seconds. The decay is analyzed in terms of the Gibbs free energy gradient for the contribution of oxygen ion migration. A relaxation model based on drift‐diffusion dynamics is presented. The model may serve as a tool for developing guidelines and design rules for future volatile memristive technology based on Schottky barrier mediated electron transport.